Andean religion research - Marzal, Manuel María (1989)
As the 20th anniversary of the Allpanchis magazine is celebrated, I have been asked to reflect on the investigation of Andean religion. This celebration is, without a doubt, a good occasion for such reflection. Those of us who, two decades ago, put our quota of enthusiasm and creativity into carrying out the project of the bishops of the Andean South to found the Andean Pastoral Institute (IPA) to support the work of the Church among the Andean population, are happy to what has been achieved, although soon it was others who took over and others the immediate goals of the first fifteen years of the IPA in Allpanchis (1984, XX:9-26).